O direto de acesso à cultura como escusa legítima para a reprodução não autorizada de obra esgotada - Leone, Elisa Gremen Mimary (2017)
The purpose of this work is to study in what circumstances and for what reasons the unauthorized full reproduction of a work which copies are sold out could be legitimately excusable. The justification for this study is the need to find a legal solution to the y y “ k” . w y hy h z that the culture access right, as it is a fundamental right and is provided in the Federal Constitution, could be used as an argument for the relativization of the prohibition. Throughout the paper, a doctrinal survey was made regarding the subject, including foreign doctrine, as a way of verifying the assertiveness of the hypothesis. After the doctrinal research and analysis of the subject, it was concluded that, not only would justification for unauthorized reproduction be based on the culture access right but also that there is a public interest involved in the satisfaction of this right, as well as some legal instruments that can be used in real cases where this relativization is necessary